Simulated versus traditional occupational therapy placements: A randomised controlled trial - Imms, C.; Froude, E.; Chu, E.; Sheppard, L.; Darzins, S.; Guinea, S.; Gospodarevskaya, E.; Carter, R.; Symmons, M.; Penman, M.; Nicola-Richmond, K.; Gilbert Hunt, S.; et al. (Wiley-Blackwell Publishing Asia, 2018)
© 2018 Occupational Therapy Australia Background/aim: Professional practise placements in occupational therapy education are critical to ensuring graduate competence. Australian occupational therapy accreditation standards allow up to 200 of a mandated 1000 placement hours to include simulation-based learning. There is, however, minimal evidence about the effectiveness of simulation-based placements compared to traditional placements in occupational therapy. We evaluated whether occupational therapy students completing a 40 hour (one week block) Simulated Clinical Placement (SCP) attained non-inferior learning outcomes to students attending a 40 hour Traditional Clinical Placement (TCP). Methods: A pragmatic, non-inferiority, assessor-blinded, multicentre, randomised controlled trial involving students from six Australian universities was conducted. Statistical power analysis estimated a required sample of 425. Concealed random allocation was undertaken with a 1:1 ratio within each university. Students were assigned to SCP or TCP in one of three settings: vocational rehabilitation, mental health or physical rehabilitation. SCP materials were developed, manualised and staff training provided. TCPs were in equivalent practice areas. Outcomes were assessed using a standardised examination, unit grades, the Student Practice Evaluation Form-Revised and student confidence survey. A generalised estimating equation approach was used to assess non-inferiority of the SCP to the TCP. Results: Of 570 randomised students (84% female), 275 attended the SCP and 265 the TCP (n = 540, 94.7% retention). There were no significant differences between the TCP and SCP on (i) examination results (marginal mean difference 1.85, 95% CI: 0.46–3.24; P = 0.087); (ii) unit score (mean (SD) SCP: 71.9 (8.8), TCP: 70.34 (9.1); P = 0.066); or (iii) placement fail rate, assessed using the Student Practice Evaluation Form-Revised (100% passed both groups). Conclusion: Students can achieve equivalent learning outcomes in a 40 hour simulated placement to those achieved in a 40 hour traditional placement. These findings provide assurance to students, educators and professional accreditation bodies that simulation can be embedded in occupational therapy education with good effect.